(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This proposed research aims to identify maternity health care services and Integrated Child Development Services of rural areas of Himachal Pradesh. India currently contributes about a quarter of worldwide figures of maternity sickness or death maternity care effectiveness and have largely considered neglected by the health care services. Particularly since the introduction of the National Rural Health Mission, the importance of efficiency of treatment become acknowledged on the policymaking and organizational stages of nationwide medical services. Integrated Child Development Services (ICDS) scheme is world’s largest community based programme and this scheme is targeted at children up to the age of 6 years, pregnant and lactating mothers and women 16–44 years of age. The scheme is aimed to improve the health, nutrition and education of the target community with the help of Anganwadi workers. ICDS is the foremost symbol of India’s commitment to its children – India’s response to the challenge of providing pre-school education on one hand and breaking the vicious cycle of malnutrition, morbidity, reduced learning capacity and mortality, on the other. This research intends to investigate current situation of maternal and treatment throughout the previous few years and will assess the strategies for maternal health care and child care in rural areas. The main objectives of the study are to know the maternity health struggles affecting rural communities, to investigate the relationship among awareness and resource usage and several maternity variables and to examine the impact of Government policies and maternity health care in rural areas. It also suggests various thrust areas for its betterment and further improvement.